Systems approach for the safety and security of hazardous chemicals. Issue 4 (18th May 2020) - Zhang, Yingyu; Sun, Chang; Shan, Wei; Junqing, Cai; Jing, Linlin; Shao, Wei
ABSTRACT: The '8.12' Tianjin Port fire and explosion are an extraordinarily major accident that involved hazardous chemicals, resulting in 165 fatalities, 798 injuries, and a direct economic loss of 6.866 billion yuan. This study introduced causal analysis based on systems theoretic accident model and process (STAMP) (CAST) to identify the key controllers in the control structure, and the control and feedback relationships among them. By using CAST, this study not only identified the traditional human and organizational factors within the physical company which are responsible for the operation process, but also identified the outside factors within the public political structure which are responsible for the public safety and security. In this study, the safety and security of hazardous chemical accident are integrated into a unified framework in which the key difference between safety and security in the intention of the actors is reframed as a general loss prevention problem. This study shows the applicability of the CAST approach in the analysis of hazardous chemical accidents and provides different perspectives and methods to develop safety and security interventions in a hazardous chemical accident.